Information Management As A Competitive Intelligence Strategy Driver - Paletta, Francisco Carlos (Journal of Sustainable Competitive Intelligence, 2014)
In this work, we focus on the role of Information Management to create additional sources of competitive intelligence that can help to prepare the organizations for sustainable growth in the long term. First, we discuss the dynamics of Information Technology and the ability to generate innovations with a direct impact on business. Then we present the need for greater balance between goals of short and long term on IT projects. In the third part, we discuss how these new technologies have helped to increase the competitiveness as well as to enhance decision-making process and the satisfaction of the end customers and stockholders. To conclude, it is presented the main challenges that the organizations will have to face in relation to the management of their information technology infrastructure, consolidation and simplification of their processes within their computing environments, aiming to increase, productivity, competitiveness, and develop agile environments that allow the organizations to meet the demands of Information Technology Governance. Keywords: Competitive Intelligence. Information Management. Information Technology Governance.